Clean color: Improving multi-filament 3D prints - Hergel, Jean; Lefebvre, Sylvain (Computer graphics forum, 2014)
Fused Filament Fabrication is an additive manufacturing process by which a 3D object is created from plastic filament. The filament is pushed through a hot nozzle where it melts. The nozzle deposits plastic layer after layer to create the final object. This process has been popularized by the RepRap community. Several printers feature multiple extruders, allowing objects to be formed from multiple materials or colors. The extruders are mounted side by side on the printer carriage. However, the print quality suffers when objects with color patterns are printed – a disappointment for designers interested in 3D printing their colored digital models. The most severe issue is the oozing of plastic from the idle extruders: Plastics of different colors bleed onto each other giving the surface a smudged aspect, excess strings oozing from the extruder deposit on the surface, and holes appear due to this missing plastic. Fixing this issue is difficult: increasing the printing speed reduces oozing but also degrades surface quality – on large prints the required speed level become impractical. Adding a physical mechanism increases cost and print time as extruders travel to a cleaning station. Instead, we rely on software and exploit degrees of freedom of the printing process. We introduce three techniques that complement each other in improving the print quality significantly. We first reduce the impact of oozing plastic by choosing a better azimuth angle for the printed part. We build a disposable rampart in close proximity of the part, giving the extruders the opportunity to wipe oozing strings and refill with hot plastic. We finally introduce a toolpath planner avoiding and hiding most of the defects due to oozing, and seamlessly integrating the rampart. We demonstrate our technique on several challenging multiple color prints, and show that our tool path planner improves the surface finish of single color prints as well.